Pengaruh Senam Dan Aerobik Terhadap Resiko Jatuh Pada Lansia Di Desa Sobokerto Kecamatan Ngemplak Boyolali Jawa Tengah - Ninik Nurhidayah (Jurnal Keterapian Fisik, 2017)
Abstract : Elders, Aerobic. Decreased physical function of the elderly causes the risk of falling. Falling in the elderly can lead to injury. Injuries that occur can lead to serious disability in the elderly. This study aims to determine to determine the effect of gymnastics and aerobics against the risk of falling in the elderly in the Village Sobokerto Ngemplak Boyolali District. The study was conducted with quasi experimental design. The sampling technique with random sampling. Total sample of 30 elderly consisting of 15 persons and 15 persons group gymnastics aerobics group. The research instrument used Tinetti test. The pre-test was conducted to determine the risk of falls of elderly before gymnastics and aerobics. Post-test performed after gymnastics and aerobics. Gymnastics and aerobics done 3 times/week for about 4 weeks with a duration of 20-30 minutes. Analysis of the data with the t-test. The significance level (= 0.05) and local criticism (dk) with dk = N - 1. The value of t count on gymnastics group is-1853, with a significance value (probability) 0.084. Therefore we can conclude there is no influence of exercise on the risk of falls in the elderly village Ngemplak Sobokerto District of Boyolali. T-count the aerobic group is -3290, with a significance value (probability) of 0.005. This means that the aerobic effect in reducing the risk of falls in the elderly Sobokerto Village District of Ngemplak Boyolali Central of Java. There is an aerobic effect on the risk of falls in the elderly village Ngemplak Sobokerto District of Boyolali.